2021
DOI: 10.2460/ajvr.82.3.237
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of intra− and postoperative variables between laparoscopic and open ovariectomy in rabbits (Oryctolagus cuniculus)

Abstract: OBJECTIVE To compare intraoperative and short-term postoperative variables pertaining to laparoscopic ovariectomy (LapOVE) and open ovariectomy (OVE) in rabbits (Oryctolagus cuniculus). ANIMALS Twelve 4− to 5-month-old female New Zealand White rabbits. PROCEDURES Rabbits were randomly assigned to undergo LapOVE (n = 6) or OVE (6), with a vessel-sealing device used to seal and transect the ovarian pedicles. Laparoscopic ovariectomy was performed with a 3-port approach. Variables were measured during surgery… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 54 publications
1
9
0
Order By: Relevance
“…27 In rabbits undergoing laparoscopic or open ovariectomy, the number and weight of feces produced and weight of food consumed postoperatively were not significantly different. 28 However, those in the open ovariectomy group spent more time eating, but not significantly so. 28 A recent study 29 in guinea pigs found that the time from anesthesia until the start of defecation and spontaneous feeding were longer in the pneumoperitoneum group in comparison to the anesthesia group.…”
Section: Discussionmentioning
confidence: 85%
See 4 more Smart Citations
“…27 In rabbits undergoing laparoscopic or open ovariectomy, the number and weight of feces produced and weight of food consumed postoperatively were not significantly different. 28 However, those in the open ovariectomy group spent more time eating, but not significantly so. 28 A recent study 29 in guinea pigs found that the time from anesthesia until the start of defecation and spontaneous feeding were longer in the pneumoperitoneum group in comparison to the anesthesia group.…”
Section: Discussionmentioning
confidence: 85%
“…28 However, those in the open ovariectomy group spent more time eating, but not significantly so. 28 A recent study 29 in guinea pigs found that the time from anesthesia until the start of defecation and spontaneous feeding were longer in the pneumoperitoneum group in comparison to the anesthesia group. However, these changes were only seen when the procedure was carried out for ≥60 minutes.…”
Section: Discussionmentioning
confidence: 85%
See 3 more Smart Citations